Fixed drug eruption caused by tadalafil - Case report - Bjekic, Milan (Sociedade Brasileira de Dermatologia, 2013)
Fixed drug eruptions (FDE) are commonly reported type of mucocutaneous drug eruption. The aim of this paper is to present a patient with multiple mucocutaneous erythema fixum type lesions caused by oral tadalafil use. A short course of topical corticosteroid therapy resulted in complete resolution of all lesions leaving residual hyperpigmentation of the involved skin sites. Mucosal oral lesions were effectively treated with gingival hyaluronic acid 0.2% gel. Conclusion: when assessing a patient of any age with drug eruptions, a thorough personal history should be obtained, in particular data on regular or recreational use of phospodiesterase type 5 inhibitors.